Surgical site infections following caesarean sections in the largest teaching hospital in Ghana - C.N. Onuzo; P.E. Sefogah; M.A. Nuamah; M. Ntumy; M.-M. Osei; K. Nkyekyer (Elsevier, 2022)
Summary: Background: Surgical site infections complicate up to 15% of all surgical procedures depending on surgery type and underlying patient status. They constitute 14-31% of all hospital-acquired infections, placing huge financial burdens on patients, healthcare institutions and the nation. Objective: To determine the incidence, risk factors, microbiological aetiology and antibiotic susceptibility patterns of surgical-site infections following caesarean sections (CSs) at Korle Bu Teaching Hospital (KBTH), Accra, Ghana. Methods: This prospective study involved 500 women who underwent CS from April to July 2017 at KBTH. Overall, 474 women completed the study with 26 women lost to follow-up or opting out of the study. Women were recruited on the first postoperative day and followed-up postnatally. Sociodemographic and obstetric data were obtained using a structured questionnaire. Swabs of infected surgical wounds were taken for culture and sensitivity testing using the Kirby-Bauer disk diffusion technique. Data was analysed using SPSS version 22. Results: Sixty-one (61/474) women (12.8%) had SSIs after CS. Of these, 41 (67.2%) were superficial, 18 (29.5%) were deep incisional and 2 (3.3%) were organ space SSIs. Significant risk factors for SSI were: emergency CS after 8 h of active labour, midline incisions, use of stored water for surgeon's pre-operative scrubbing, maternal status being single and alcohol consumption during pregnancy. Staphylococcus aureus was the commonest pathogen isolated with 6 (9.8%) being meticillin resistant (MRSA). Antibiotic susceptibility was mostly to quinolones. Conclusion: SSI occurred in 12.8% of CS wounds at the KBTH, commonly caused by S. aureus.